2018
DOI: 10.1097/bpo.0000000000000775
|View full text |Cite
|
Sign up to set email alerts
|

Flexible Intramedullary Nails for Femur Fractures in Pediatric Patients Heavier Than 100 Pounds

Abstract: Therapeutic Level III.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 31 publications
0
17
0
Order By: Relevance
“…11 However, recently, more data have emerged on the applicability of flexible nailing in the heavier (.100 lb) patient, and it has been as successful as the lighter cohort. 13 This methodology has previously been verified for quicker mobilization in children, 14 so with the limitations imposed by our patient's condition, we felt that flexible nailing could stabilize her fracture while allowing for less pain with transfers. The mindset on the feasibility of flexible nailing in the pediatric cohort has been focused on the adaptability of the nail diameters to the narrow canal size coupled with the improved ability of children to heal fractures based on secondary bone healing.…”
Section: Discussionmentioning
confidence: 70%
“…11 However, recently, more data have emerged on the applicability of flexible nailing in the heavier (.100 lb) patient, and it has been as successful as the lighter cohort. 13 This methodology has previously been verified for quicker mobilization in children, 14 so with the limitations imposed by our patient's condition, we felt that flexible nailing could stabilize her fracture while allowing for less pain with transfers. The mindset on the feasibility of flexible nailing in the pediatric cohort has been focused on the adaptability of the nail diameters to the narrow canal size coupled with the improved ability of children to heal fractures based on secondary bone healing.…”
Section: Discussionmentioning
confidence: 70%
“…6 Small comparative studies consisting of only stainless steel flexible nails suggest that their use may be acceptable in patients who weigh 100 pounds or more or have a length-unstable fracture. 30,31 In summary, proper patient selection and surgical management of implants during flexible intramedullary nail placement (eg, choice of metal, canal fill, and implant management at entry sites) is important. Atassi et al 32 recently reported low complication rates in a series of 101 fractures treated with flexible intramedullary nails (of which they defined 50% as "unstable").…”
Section: Flexible Intramedullary Nailsmentioning
confidence: 99%
“…6 Small comparative studies consisting of only stainless steel flexible nails suggest that their use may be acceptable in patients who weigh 100 pounds or more or have a length-unstable fracture. 30,31…”
Section: Flexible Intramedullary Nailsmentioning
confidence: 99%
“…Stainless-steel nails are more rigid and are often stacked to enhance canal filling [55]. Hence, many recommend the use of the more rigid stainless-steel nails for the treatment of fractures in heavier patients [57]. Proper surgical technique is also required to for optimal rotational, axial, and translational stability in these patients [5].…”
Section: Elastic Stable Intramedullary Nailing (Esin)mentioning
confidence: 99%